Răspunsuri

2014-11-01T19:09:47+02:00
A) x+2y+y-3z=x+3y-3z=17+4=21
b) 3(x+2y)-2(y-3z)=3•17-2•4=43
c) 2(x+2y)+y-3z=34+4=38
d) 2(x+2y)•[x+2y+2(y-3z)]=34•(17+8)=950
3 4 3
2014-11-01T19:12:15+02:00
A) x + 2y + y - 3z = 17 + 4  = 21
b) 3(x + 2y) + 2(y - 3z) = 3 * 17 + 2 * 4 = 51 + 8 = 59
c) 2(x + 2y) + (y - 3z) = 2 * 17 + 4 = 34 + 4 = 38 
d) intre paranteze este minus?
2(x + 2y) - [(x + 2y) + 2(y - 3z)] = 2 * 17 - (17 + 2 * 4) = 34 - 25 = 9
sau este inmultit
2(x + 2y) * [(x + 2y) + 2(y -3z)] = 2 * 17 * (17 + 2 * 4) = 34 * 25 = 850
3 4 3